(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
Three natural bioactive compounds, viz. cow dung, bee propolis and turmeric powder were applied to amend the Ralstonia solanacearum infested soil of potato. Sun dried cow dung @ 30 t/ha, aqueous extraction of turmeric powder @ 30 kg/ha and propolis @ 5 lit/ha were applied to the inoculated soil by mixing with field soil in SAU (Dhaka) and BARI (Gazipur). Data on pH, organic matter, total cfu/ml and avirulent cfu/ml of the treatment applied soil and per cent disease index (PDI) of bacterial wilt of potato were recorded. Significant difference in soil pH and per cent organic matter (OM) occurred in all the amended soil as compared to control. A decreased total cfu/ml of R. solanacearum occurred in all the treated soil, but propolis (8.2 X 107) and cow dung (1.1 X 108) showed the lowest count. However, in increasing the avirulent count of R. solanacearum, turmeric powder (1.8 X 109) showed the highest count compared to other amended soil. Significant disease reduction over control was also observed in all the treatments, but propolis (45.65%) and turmeric powder (43.48%) showed the best results in wilt disease reduction. J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(1): 43-50